2008
DOI: 10.1111/j.0018-0661.2008.02011.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Turkish local grape accessions (Vitis vinifera L.) using RAPD markers

Abstract: To estimate genetic relationships among 46 local grape cultivars, RAPD analysis was performed with 25 decamer primers selected from a total of 60 primers. Genetic relationships among these cultivars were determined by calculating similarity indexes, from which a dendogram was derived. There was high genetic variation among the cultivars, with values of genetic diversity ranging from 0.553 to 0.952 using the Jaccard coefficient. UPGMA analysis of a distance matrix produced a dendogram with six clusters. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
1
4
0
1
Order By: Relevance
“…In this study, the general similarity ratios among the cultivars were found to be between 0.650 and 0.900, showing a parallelism with the other RAPD analyses performed by other researchers, 0.553-0.952 (Ergül et al, 2002;Karataş, 2005;Ağaoğlu et al, 2006;Karataş and Ağaoğlu, 2008).…”
Section: Resultssupporting
confidence: 89%
“…In this study, the general similarity ratios among the cultivars were found to be between 0.650 and 0.900, showing a parallelism with the other RAPD analyses performed by other researchers, 0.553-0.952 (Ergül et al, 2002;Karataş, 2005;Ağaoğlu et al, 2006;Karataş and Ağaoğlu, 2008).…”
Section: Resultssupporting
confidence: 89%
“…Outside, for some non comprehensive reasons, the genetic variability between accessions of Calligonum is due to the occupied different specific geographical places, and therefore to their capacities to adjust to the specific climatic conditions. The survey of germplasms of the Turk grape suggested that the geographical and ecological distribution of plants contributes to a high genetic variability (Karatas and Agaoglu, 2008). According to Liu and Pei, (1999) and Runo et al (2004), the similar strips gotten by RAPD from different individuals are not necessarily homologous, although, they can share the same dimension in pairs of basis.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons many fruit tree crops have been successfully fingerprinted using RAPD markers, e.g. grape (Huseyin and Sabitagaoglu, 2008), strawberry (Sugimoto et al, 2005), olive (Sanz-Cortes et al, 2001) and pineapple (Sripaoraya et al, 2001). However, despite its limitations such as sensitivity to reaction conditions, problems with repeatability, and amplification of non-homologous sequences, it has been successfully used for the assessment of genetic diversity in plants (Maria et al, 2008).…”
Section: Introductionmentioning
confidence: 99%